2013
DOI: 10.1136/heartjnl-2013-303624
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of cardiovascular magnetic resonance in the diagnosis of coronary heart disease: an economic evaluation using data from the CE-MARC study

Abstract: The CE-MARC study showed that CMR had superior diagnostic accuracy to SPECT and concluded that CMR should be more widely used in the investigation of patients with CHD. The economic evaluation results show that using CMR is also a cost-effective strategy and supports the wider adoption of this modality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 24 publications
3
78
0
1
Order By: Relevance
“…Myocardial perfusion magnetic resonance imaging (MRI) is increasingly used as an accurate and reproducible technique for noninvasive diagnosis of coronary heart disease (CHD). Its potential advantages include a lack of ionizing radiation exposure, cost‐effectiveness, and additional information on cardiac anatomy, function, and tissue viability when performed as part of a multiparametric protocol 2, 3. Magnetic resonance (MR) perfusion imaging has high sensitivity and specificity as compared to x‐ray coronary angiography 4.…”
mentioning
confidence: 99%
“…Myocardial perfusion magnetic resonance imaging (MRI) is increasingly used as an accurate and reproducible technique for noninvasive diagnosis of coronary heart disease (CHD). Its potential advantages include a lack of ionizing radiation exposure, cost‐effectiveness, and additional information on cardiac anatomy, function, and tissue viability when performed as part of a multiparametric protocol 2, 3. Magnetic resonance (MR) perfusion imaging has high sensitivity and specificity as compared to x‐ray coronary angiography 4.…”
mentioning
confidence: 99%
“…The recently published CE-MARC study established the superior diagnostic accuracy of cardiac MR over Singlephoton emission computed tomography (SPECT) and further cost-effectiveness analysis also proved its superiority as a diagnostic tool for ischemic heart disease [35].…”
Section: Perfusion Imaging-role Of Microvascular Obstructionmentioning
confidence: 99%
“…Recovery of function after revascularization appears to be related to the ratio of viable-to-scarred myocardium within dysfunctional myocardial segments. Different cutoff values for transmural extent of hyperenhancement have been applied to determine whether or not functional recovery post-revascularization can be expected, ranging from[0 % to [ 75 % [35]. Due to its superior spatial resolution, LGE by MRI is better than SPECT and Positron emission tomography (PET) at identifying regions of subendocardial scar [41].…”
Section: Cine Imagingmentioning
confidence: 99%
“…35 Subanalysis of the original study indicated that cMRI is a cost-effective test and supported more widespread use of the modality. 36 Direct comparison to SPECT further benefits cMRI for its lack of ionizing radiation dose and higher spatial resolution. Increased sensitivity over SPECT has been shown in the IMPACT 1 study 32 especially for small, non-transmural or subendocardial infarcts.…”
Section: Cardiac Mr Perfusion Imagingmentioning
confidence: 99%